If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3g + -8(g + -8) = 42 Reorder the terms: 3g + -8(-8 + g) = 42 3g + (-8 * -8 + g * -8) = 42 3g + (64 + -8g) = 42 Reorder the terms: 64 + 3g + -8g = 42 Combine like terms: 3g + -8g = -5g 64 + -5g = 42 Solving 64 + -5g = 42 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-64' to each side of the equation. 64 + -64 + -5g = 42 + -64 Combine like terms: 64 + -64 = 0 0 + -5g = 42 + -64 -5g = 42 + -64 Combine like terms: 42 + -64 = -22 -5g = -22 Divide each side by '-5'. g = 4.4 Simplifying g = 4.4
| log(3x+1)=1 | | 4d^5=10y | | log(3x+1)+6=7 | | 8x+9*0=72 | | 28+yi=21-x+7i | | 7x-5y=-21 | | x-1.2-2=5 | | -4(4x-3)=-5x+23 | | 252=k*2*36 | | (x+11)(2x+5)=117 | | z-57=-67 | | 1a+7+8a+1+2a+3a+2=218 | | 5x+3x+2x=84000 | | 7/10z-33/5=2/5 | | -6x+9+2x=49 | | 3(y-4)+2y=y-4 | | 500-500=500 | | 0.36=log(x) | | 0=3.5t^2-24t-140 | | 4x^2-39x+27=0 | | y^4-82y^2+81=0 | | 2(1-5r)-4=14-2r | | 9-12x=36 | | f+7=9-2 | | 2n-11-2=-13 | | 7x+3+2=-33 | | 9x-12=36 | | -9x+6x-1=0 | | .50t+2=16 | | 2n-11-2= | | 2*8-11-2= | | 4x-16=2(x+3) |